Hubungan Kualitas Tidur dengan Kejadian Dismenore Pada Siswi di SMK Negeri 5 Kendal - Terris Nur Fadhila; Kristina Maharani; Agnes Isti Harjanti (Lembaga Pengembangan Kinerja Dosen, 2025)
The incidence of dysmenorrhea in Indonesia is 107,673 individuals (64.25%), consisting of 59,671 individuals (54.89%) experiencing primary dysmenorrhea and 9,496 individuals (9.36%) experiencing secondary dysmenorrhea. In Kendal Regency, the number of adolescent girls experiencing dysmenorrhea in 2014 was 11,570, while in 2015, the number was 11,565 (29.8%).Several factors that trigger the increase in the incidence of dysmenorrhea among adolescents include sleeping quality. This study determined the correlation between sleeping quality and the incidence of dysmenorrhea in adolescents at Public VHS 5 Kendal. The research used observational analytics with a cross-sectional approach. The population in this study consisted of 10th and 11th-grade female students. The sampling technique was purposive sampling, resulting in a sample size of 63 respondents. The statistical test was the normality test using the Kolmogorov-Smirnov method followed by the Wilcoxon test, and a p-value of 0.000 was obtained, accepting Ha or indicating a correlation between sleeping quality and the incidence of dysmenorrhea among female students at Public VHS 5 Kendal. The researcher expects the results of this research can serve as educational material on the importance of consistently maintaining sleep quality to prevent worsening dysmenorrhea.